(untitled) (Global Journal of Medical Research, 2014)
Foot-and-mouth disease is a highly contagious viral disease of the cloven-hoofed animals leading to severe economic losses to livestock industry. The disease is clinically characterized by pyrexia, vesicles on the mouth, muzzle, tongue, teats, inter digital space etc with high morbidity and low mortality in affected adults. However, the immune-suppression due to Foot-and-mouth disease virus may lead to development of secondary bacterial infection in the affected animals as a cause of mortality. Many of such secondary bacterial invaders have been reported. The present study revealed Pseudomonas spp. as monoculture from an outbreak leading to mortality in cattle and buffaloes. Pseudomonas aeruginosa, a ubiquitous bacterium, known to cause nosocomial infections such as pneumonia, urinary tract infections, and respiratory system infections are supposed to produce high case fatality rate in immunesuppressed host due to severe toxaemia and drug resistance. The isolates were subjected to antibiotic sensitivity test.